1989
DOI: 10.1063/1.858998
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear magnetohydrodynamic studies of the tilt mode in field-reversed configurations

Abstract: A three-dimensional magnetohydrodynamic code has been used to study the nonlinear evolution of the tilt instability in a field-reversed configuration. The evolution of the mode has been followed through magnetic field reconnection to complete the loss of confinement, with no evidence of any nonlinear stabilizing effects. The influence of plasma rotation has also been investigated. It was found that while the mode remains unstable, its character changed at high rotation rates. It evolves from an internal mode w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…In MHD calculations including the effect of gyro-viscosity 5 , up to a factor of 3 reduction in growth rate has been found, but not complete stability. It has also been found that there is no nonlinear saturation of the n = 1 tilt instability in the MHD description 2,7 .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In MHD calculations including the effect of gyro-viscosity 5 , up to a factor of 3 reduction in growth rate has been found, but not complete stability. It has also been found that there is no nonlinear saturation of the n = 1 tilt instability in the MHD description 2,7 .…”
Section: Introductionmentioning
confidence: 97%
“…A substantial literature exists of FRC stability studies in both the MHD (ie, fluid) and kinetic (ie, particle ion) descriptions [2][3][4][5][6][7][8][9] . The n = 1 tilt instability is thought to be the most dangerous MHD instability because it is both strongly growing and a global mode that is not readily stabilized when kinetic effects are included.…”
Section: Introductionmentioning
confidence: 99%
“…The simulations in Ref. 9 were performed for FRCs with a racetrack separatrix shape, which could possibly account for the disagreement with the variational studies 4,6 . We were motivated to 5 study the Hall-MHD stability for a class of elliptic configurations, which have been suggested to have favorable stability properties 14 .…”
Section: Effects Of the Hall Termmentioning
confidence: 99%
“…The discrepancy is even stronger for configurations with large E and racetrack-like separatrix shapes 7 . Moreover, several self-consistent numerical calculations [8][9][10][11] , including FLR or Hall effects, as well as a fully kinetic ion description, find that the n = 1 tilt mode remains linearly unstable even in the highly kinetic regime: S * /E ∼ 1.…”
Section: Introductionmentioning
confidence: 99%
“…Velocity-space diffusion is computed using the Rosenbluth form of the Fokker-Planck oper-ator [ll], with the potentials found by first using the Green's function to get the potentials on a numerical boundary in velocity space and then finding the interior solution by Poisson solves using an iterative method [12]. To accomplish the bounce averaging, the unknown distribution function is first represented as a function of the constants of the motion for a spherically symmetric system, that is, the total energy and the total angular momentum.…”
Section: Theoretical Analysismentioning
confidence: 99%